Study of erosion corrosion in oil and gas industry - Hasyim Salleh (Universiti Malaysia Perlis, 2009)
This project is about study of the erosion corrosion in oil and gas industries based on the samples from Petronas Gas Processing Plant. The microstructure and hardness analysis was done to the sample ASTM A 105 Carbon Steel (elbow that failed due to erosion corrosion). Found that the microstructure and hardness of failed samples was altered and different compared to new sample (with same grade of carbon steel). Experiment on erosion corrosion was design in order to get more understanding on erosion corrosion mechanism. Result of experiment shown weight loss of the sample is 6 grams for 37 hours experiment. In order to measured corrosion rate of the sample, tafel plot (electrochemical techniques of corrosion measurement) was run by using Gamry Instruments. From data gathered, the corrosion rate of ASTM A 105 carbon steel in Sodium Chloride environment is 3.070682E-03 millimeter per year (mm/year).